OPENING THE EYE OF LOVE: James Purdy's Ethical Allegory - Adams, Don (Journal of Dharma, 2020)
This essay examines James Purdy's 1975 ethical and allegorical religious novel, In A Shallow Grave, from the viewpoint of negative theology. Purdy's tendency toward negation of the conventional actual-world correspondences of mimetic realism has contributed to the misreading and undervaluing of his visionary ethical fiction. But when Purdy's allegorical-realist texts are approached from the enabling metaphysical and spiritual perspective of the via negativa, as explored in this essay through the writing of Pseudo-Dionysius and Pope Benedict XVI, the fiction's mimetic contrariness may be revealed as the vehicle of ethical instruction and metaphysical revelation. The gist of the novel's ethical instruction concerns the primacy of love in human nature and relations, and the novel's metaphysical revelation is the vision of being's ultimate harmony that is gradually revealed to the eye of love through the insistent negation of our conventional egoistic assumptions regarding self and world.